(untitled) (Global Journal of Science Frontier Research, 2018)
Qena-Quseir shear zone area is located at the central part of the Eastern Desert covering area of about 9460 Km 2 . This area is mainly covered by basement rocks however there are parts covered by sedimentary rocks ranging in age from Upper Cretaceous to Quaternary. High-resolution magnetic data can be used as a good tool to delineate the basement surface; explain many structure features such as faults, lineaments, joints and lithological features. In this research work, high resolution imaging methods, inversion and feature extraction techniques have been applied on airborne magnetic data collected over Qena-Quseir shear zone area. Two techniques of depth calculations were applied to the aeromagnetic data of the study area. The first look to the two maps show that their results are much closed to each other. In the two maps, the western part of the area shows more deeper depth to basement representing thicker sedimentary section.